MAKNA SIMBOLIK TARI SONTOLOYO GIYANTI KABUPATEN WONOSOBO (Universitas Negeri Semarang, 2013)
Sontoloyo dance is a traditional dance that became the basis of the dance mask dance Leng- ger Giyanti. This dance contains a mockery of the fragility of the ruler as well as religious symbols of Islam. The purpose of this study to understand and describe the symbolic mea- nings that exist in Sontoloyo dance. This study is qualitative and descriptive research. The collection of data using observation techniques, interviews and documentation. Data analysis was performed by means of data reduction, data presentation, the validity of the data using triangulation of data and drawing conclusions. The results show that dance is a traditional dance popular Sontoloyo depicting the valor of soldiers. Dance Sontoloyo have symbolic mea- ning contained in the motion, songs, property and accompanying music. Motion used in the dance Sontoloyo is: mincet, lampah sekar, jinjitan, golekan, ngencek, blows and move sekar pacak Gulu. Dance has some symbolic meaning, that is: religious meaning, the meaning of solidarity and mutual cooperation, the meaning of knights and responsibilities, as well as the meaning of satire against the ruling. Sontoloyo accompaniment of dance has a meaning: the compactness and the knights, and responsibility, and innuendo. Sontoloyo dance makeup implies: valor and courage, beauty and neatness. Sontoloyo fashion dance has a meaning: a person’s status, accuracy, authority, and valor, satire and beauty. Fashion colors have mea- ning: a protest against the arbitrariness of the authorities, sarcasm, happiness, anger and turmoil liver.